Nigerian Writers as Social Critics: A Study of the Poetry of Niyi Osundare and Ezenwa-Ohaeto (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
There is a close symbiosis between literature and society. One can say that both of them are two sides of a coin. Writers derive their inspiration from the society and this explains the social realities that pervade the literary productions of writers from Nigeria in particular and Africa in general. Since Nigerian independence, Nigerian writers have explored social issues that bedeviled the society. Notable among them is bad leadership and experiences show that bad leadership is the bane of Nigerian society. This research reemphasizes/re-echoes the menace of bad leadership in Nigerian Society and how Nigerian writers have made efforts at “righting” this anomaly through its condemnation in their literary productions. This paper studied Songs of the Season by Niyi Osundare and Songs of a Traveler by Ezenwa-Ohaeto. The analysis revealed that these poets under study are committed writers who used their works for the betterment of Nigerian society. The paper is hinged on Georg Lukacs’ Reflection theory.  The basic assumption of this theory is that a text will reflect the society that has produced it and this is what the poets under study did in their collections of poetry. The paper concluded on the note that bad leadership affects every section of the society. Again, it shows that some political leaders in Nigeria are found wanting in this regard. The paper suggests that all hands should be on deck to reduce its occurrence or better still, promote actions that will lead to its annihilation from the Nigerian society.
Keywords: Bad Leadership; Nigerian Poetry; Society; Social Reality; Anomaly